2020
DOI: 10.1016/j.thromres.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of thrombotic complications in critically ill ICU patients with COVID-19

Abstract: Introduction: COVID-19 may predispose to both venous and arterial thromboembolism due to excessive inflammation, hypoxia, immobilisation and diffuse intravascular coagulation. Reports on the incidence of thrombotic complications are however not available. Methods: We evaluated the incidence of the composite outcome of symptomatic acute pulmonary embolism (PE), deep-vein thrombosis, ischemic stroke, myocardial infarction or systemic arterial embolism in all COVID-19 patients admitted to the ICU of 2 Dutch unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

177
4,812
40
331

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 4,566 publications
(5,566 citation statements)
references
References 5 publications
177
4,812
40
331
Order By: Relevance
“…Thus, the extrinsic pathway of coagulation is activated in plasma throughout the pulmonary vasculature, resulting in the clinical picture of local coagulation [59]. Obstruction of pulmonary capillaries by thrombi and local inflammatory vasodilation contributes to veno-arterial shunt and profound hypoxia observed in the severe COVID-19 patients [15,42,59,60]. The process is limited by the immune status of the patient as the mechanisms described above accelerate into vicious positive feedback loops.…”
Section: The Covid-19 Lung Pathologymentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the extrinsic pathway of coagulation is activated in plasma throughout the pulmonary vasculature, resulting in the clinical picture of local coagulation [59]. Obstruction of pulmonary capillaries by thrombi and local inflammatory vasodilation contributes to veno-arterial shunt and profound hypoxia observed in the severe COVID-19 patients [15,42,59,60]. The process is limited by the immune status of the patient as the mechanisms described above accelerate into vicious positive feedback loops.…”
Section: The Covid-19 Lung Pathologymentioning
confidence: 99%
“…Initial reports from China, reported patients suffering from a severe or fatal COVID-19 disease course, with slightly lower platelet count and a higher level of d-dimer [41,62]. But it was the first reports from Italy and other European countries, which emphasized the remarkably high incidence of pulmonary embolism and thrombosis in the most severe and fatal cases [59,60,63]. At present, there is an awareness of a few clinical and laboratory features of patients with COVID-19, which is thrombocytopenia, elevated d-dimer level, prothrombin time prolongation and disseminated intravascular coagulation [64,65].…”
Section: Coagulation and Thrombosis In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the expression of ACE2 in the lining of blood vessels is of note, as it could contribute to the risk of thrombotic events in patients with COVID-19, potentially via virion entry causing endothelial inflammation. 6 In addition, the interaction between ACE2 and the coronavirus virion could act as a target for vaccines. For example, a recent study characterising the receptor-binding domain of the viral spike protein, which interacts with ACE2, suggested that this protein could be used as a vaccine target which would prevent COVID-19 infection.…”
Section: Ace2 and Its Role In Covid-19mentioning
confidence: 99%